2019
DOI: 10.2174/1573397114666181016112342
|View full text |Cite
|
Sign up to set email alerts
|

Selenium and Autoimmune Diseases: A Review Article

Abstract: Background: Selenium is an essential trace element with fundamental effects on human biology. Trace elements deficiency is not an uncommon finding in autoimmune diseases. This deficiency may be a consequence of autoimmune diseases or may contribute to their etiology. With regard to evidence showing the association between selenium deficiency and generation of reactive oxygen species and subsequent inflammation, reviewing the role of selenium in collagen vascular diseases could help researchers to devise strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 47 publications
0
30
0
Order By: Relevance
“…These types of enzymes participate in the regulation of the oxidative and inflammatory state, and it has previously been considered as a factor that affects the disease activity. Nevertheless, it is unclear whether Se deficiency is a cause or consequence of autoimmune diseases [ 84 ]. In RA, it has been stipulated with more consistency among the studies addressed in this review, that this phenomenon is caused by inflammation [ 86 , 94 , 96 , 98 , 99 ]; however, other studies suggested that deficiency of this trace element in the diet could be the cause of low levels of Se in serum [ 55 , 92 , 100 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These types of enzymes participate in the regulation of the oxidative and inflammatory state, and it has previously been considered as a factor that affects the disease activity. Nevertheless, it is unclear whether Se deficiency is a cause or consequence of autoimmune diseases [ 84 ]. In RA, it has been stipulated with more consistency among the studies addressed in this review, that this phenomenon is caused by inflammation [ 86 , 94 , 96 , 98 , 99 ]; however, other studies suggested that deficiency of this trace element in the diet could be the cause of low levels of Se in serum [ 55 , 92 , 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, decreased serum concentration of trace elements has been described as a common occurrence in autoimmune diseases [ 81 , 82 , 83 ]. Nevertheless, although it has not been clarified whether Se deficiency is a cause or consequence of the development of these diseases, its deficiency could be a factor for the progression of RA, because it has been associated with the generation of ROS and the associated inflammatory state [ 84 ]. Several studies that evaluated the serum concentration of this trace element in patients with RA reported lower concentrations compared to that of apparently healthy individuals ( Table 3 ) [ 55 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 ].…”
Section: Serum Selenium Status In Rheumatoid Arthritismentioning
confidence: 99%
“…In Kashin-Beck disease, increased levels of IL-6, IL-1β and TNF-α were found in selenium-depleted individuals [ 102 ]. In a systematic review of 32 studies of autoimmune diseases, such as rheumatoid arthritis and vasculitis, significantly lower serum selenium concentration was identified in cases than in controls [ 103 ], though the direction of causality was unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Seleniun de ciency has been proposed for decades as the archetypal etiological theory of KBD [6][7][8].…”
Section: Introductionmentioning
confidence: 99%